Supply chain (Boston, Massachusetts : Harvard Business Review Press, 2023)
"Supply and demand shocks. Labor shortages. International trade wars. As businesses and customers struggle to get the products they need from across the globe, manufacturers must reassess how they operate, from considering domestic suppliers to exploring new technologies. In Supply Chain: The Insights You Need from Harvard Business Review, articles by experts and researchers will help you understand the risks and identify solutions to these disruptions so that you can ensure a more resilient supply chain-without sacrificing competitive advantage"--
Steps to Prepare Your Supply Chain for the Next Crisis : Risk is more predictable than you might think / by ChrisIan Schuh, Wolfgang Schnellbächer, and Daniel Weise -- Why It's So Hard to Map Global Supply Chains : Understand your connection to the broader supply network / by Vishal Gaur, Nikolay Osadchiy, and Maximiliano Udenio -- Don't Abandon Your Just-In-Time Supply Chain-Revamp It : Build buffers, not stockpiles / by ManMohan S. Sodhi and Thomas Y. Choi -- Small Businesses Play a Big Role in Supply-Chain Resilience : They can strengthen systemic productivity, collaboration, and comptitiveness / by Karen G. Mills, Elisabeth B. Reynolds, and Morgane Herculano -- Leveraging New Tech to Bring Supply Chain Closer to Home : Use an artificial intelligence + human intelligence approach / by Suketu Gandhi -- Trade Regionalization: More Hype Than Reality? : Research shows that goods actually traveled farther after the pandemic / by Steven A. Altman and Caroline R. BasIan -- A Better Way to Match Supply and Demand in the Retail Supply Chain : Stop forecasting and start flow-casting / by Mike Doherty and George Stalk, Jr. -- How to Turn a Supply Chain Plaform into an InnovaIon Engine : Lessons from Haier / by Kasra Ferdows, Hau L. Lee, and Xiande Zhao -- In Uncertain Times, Big Companies Need to Take Care of Their Suppliers : Move beyond transactional relationships / by Willy C. Shih -- Digital Transformation Is Changing Supply Chain RelaIonships : Become a boundary spanner / by Maria Jesús Saénz, Elena Revilla, and Inma Borrella -- How Walmart Automated Supplier Negotiations : AI can benefit both buyers and suppliers / by Remko Van Hoek, Michael DeWitt, Mary Lacity, and Travis Johnson -- Consumer Pressure Is Key to Fixing Dire Labor CondiIons : Tips from the clothing industry for improving transparency, while pushing for ethical standards / by Robert Handfield, Tim Kraft, and Marguerite Moore -- A More Sustainable Supply Chain : Uncovering risks in your lower tier
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 15, 2023).
WorldCat record variable field(s) change: 050
Keywords: Business logistics; Industrial management; Success in business; Business logistics; Industrial management; Success in business; elektronické knihy; electronic books